2018
DOI: 10.1002/cae.22006
|View full text |Cite
|
Sign up to set email alerts
|

An educational tool to improve understanding of structural dynamics through idealization of physical structure to analytical model

Abstract: An innovative computer‐aided educational tool for structural dynamics entitled “SDET” is developed to help students understand the idealization of the physical structure into a single‐degree‐of‐freedom (SDOF) system with five predefined example templates. The SDOF system then can be analyzed for a different combination of initial conditions and loadings using SDET. This tool can enhance the teaching/learning process leading to increase in engineering judgment and physical understanding of mathematical concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The local mass matrix of a 3D beam element is implemented according to Equation (9) to Equation (14), where E is the material Young's modulus, G is the material shear modulus, S A is the cross-section effective shear area, I is the crosssection moment of inertia, and J is the cross-section polar moment of inertia. The matrix is decomposed into an Euler-Bernoulli component, EB e M , and a Timoshenko component, Tim e M .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The local mass matrix of a 3D beam element is implemented according to Equation (9) to Equation (14), where E is the material Young's modulus, G is the material shear modulus, S A is the cross-section effective shear area, I is the crosssection moment of inertia, and J is the cross-section polar moment of inertia. The matrix is decomposed into an Euler-Bernoulli component, EB e M , and a Timoshenko component, Tim e M .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Previous studies have reported on the use and benefits of mobile learning for students' performance and motivation in K-12 education [26,47]. Moreover, examples of mobile learning tool development and use within several engineering disciplines, including acoustics and vibrations [48], computer science [36], and structural dynamics [44], signal emerging acceptance of mobile learning within postsecondary engineering education. Although we found that available literature related to the development of mobile PIV learning tools for fluid mechanics education was limited (we did not find any in our search), our literature search did reveal work related to the development of a mobile PIV tool for the industrial fluid mechanics application of measuring surface flows (i.e., of rivers and discharges) during extreme weather events such as floods [10].…”
Section: Mobile Instructional Pivmentioning
confidence: 99%
“…To date, computer‐aided educational platforms have been widely implemented in engineering courses to facilitate the teaching and learning process. Sonparote and Mahajan [30] developed a platform to demonstrate structural dynamics using JAVA [15]. A platform software prepared in the DELPHI environment was developed by Gencer and Gedikpinar [16] to be utilized in laboratories of electric machinery courses.…”
Section: Introductionmentioning
confidence: 99%